Hypertension in children and adolescents: new perspectives - Lurbe, Empar; Wühl, Elke (Springer, 2019)
1 Introduction -- 2 From pregnancy to childhood and adulthood: The trajectory of hypertension -- 3 Perinatal programing and blood pressure -- 4 Worldwide overview about the prevalence and trends of hypertension in Children and Adolescents -- 5 Office and out of office blood pressure measurements -- 6 Large vessels in hypertension: Central blood pressure -- 7 Isolated systolic hypertension -- 8 Secondary hypertension: Diagnostic and treatment -- 9 Monogenic hypertension -- 10 Neonatal hypertension -- 11 The heart in hypertension -- 12 The kidney in hypertension -- 13 No pharmacological treatment of hypertension -- 14Pharmacological approach to hypertension treatment -- 15 Physical exercise in the treatment of obesity: New approach to individualize treatment -- 16 Treatment of hypertension in chronic kidney disease -- 17 Long term follow up -- 18 Clinical trials